Application of activated carbon fabric for the removal of a recalcitrant pesticide from agricultural run-off - Cosgrove, Stephanie; Jefferson, Bruce; Jarvis, Peter (Elsevier, 2022)
Removal of pesticides from agricultural run-off close to the point of application has the potential to prevent or reduce the pollution of water sources used for drinking. This research considered the novel application of activated carbon (AC) fabric as a sorbent material for removal of pesticides from field run-off. AC fabric was tested for the removal of the molluscicide pesticide metaldehyde under a range of flow rates at both laboratory and pilot scale. Metaldehyde at an initial concentration of 10 μg/L was removed effectively from deionised (DI) water and real source water by the AC cloth under all conditions tested, reaching removal of 1375 and 876 μg/g (equivalent to 169 and 264 mg/m2), respectively. The adsorption followed pseudo-second order kinetics (k2 of 29.9 and 34.8 g/μg min for the AC fabric and GAC), providing rapid removal of metaldehyde within the first 5 min of contact. In single pass and flow through conditions, stabilised removal of 46% metaldehyde was achieved by the AC fabric bundle for treatment of 700 L of real water in a pilot scale flume. This equated to removal of 454 μg/m2, although significantly more removal would be expected over longer duration testing given the stabilised removal and the equilibrium capacity of the fabric seen during the batch isotherm testing. The work provides evidence to show that AC fabric could be used in the catchment to reduce peak loads of pesticides in sources used for drinking water.
Keywords: Pesticides; Metaldehyde; Water quality; Adsorption; Activated carbon cloth; Drinking water